Analisis Pemberian ASI Eksklusif Terhadap Kejadian Stunting Pada Balita Usia 6-24 Bulan di Desa Besuk Kecamatan Klabang Bondowoso - Nafisa, Wildatin; Yulifah, Rita; Susilawati, Susilawati (Jember Maternal and Child Health Journal, 2024)
Background: Stunting occurs when a child's length or height is far below average due to growth and development conditions caused by chronic hunger and frequent illnesses. Until 2022, the percentage of toddlers with stunted growth was 21.6% nationally, 19.2% in East Java Province, and 32.0% in Bondowoso Regency. The purpose of this study was to examine the correlation between stunting rates and the availability of exclusive breastfeeding. Method: A cross-sectional technique based on observational analytics was used in this study design. Mothers with toddlers aged 6-24 months became the study population; 40 mothers were selected using a simple random sampling procedure. Information was collected through a survey. Chi-Square test data analysis. Results: 70% of respondents did not provide exclusive breastfeeding to toddlers and the proportion of stunting incidents was 52.5%. In this study, the significance level ?-value = 0.003 <? 0.05, which means there is a relationship between exclusive breastfeeding in toddlers and the incidence of stunting. Conclusion: The correlation between exclusive breastfeeding and the prevalence of stunting is likely caused by the high calcium content in exclusive breastfeeding which is effectively absorbed by the body so that growth, especially height, can run optimally and reduce the risk of stunting.